2005
DOI: 10.4269/ajtmh.2005.72.540
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Infection and Cognitive Impairment Among Filipino Children

Abstract: The objective of this study was to examine the independent effect of infection with each of four helminths (Ascaris lumbricoides, Schistosoma japonicum, Necator americanus, and Trichuris trichiura) on cognitive function after adjusting for the potential confounders nutritional status, socioeconomic status (SES), hemoglobin, sex, and the presence of other helminthes. This cross-sectional study was carried out in a rural village in Leyte, The Philippines in 319 children 7-18 years old. Three stools were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
154
2
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(176 citation statements)
references
References 48 publications
12
154
2
8
Order By: Relevance
“…[1][2][3] Observational studies have found that chronic infection with STHs among school-aged children is associated with malnutrition and impaired growth, 4-6 cognitive impairment, 7,8 and lower school attendance. 9 These associations suggest that, in theory, reducing STH infection in children has the potential to improve nutrition and growth (i.e., hemoglobin levels, weight, height), cognitive abilities (i.e., working memory, processing speed), and school performance (i.e., school attendance, standardized test scores).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Observational studies have found that chronic infection with STHs among school-aged children is associated with malnutrition and impaired growth, 4-6 cognitive impairment, 7,8 and lower school attendance. 9 These associations suggest that, in theory, reducing STH infection in children has the potential to improve nutrition and growth (i.e., hemoglobin levels, weight, height), cognitive abilities (i.e., working memory, processing speed), and school performance (i.e., school attendance, standardized test scores).…”
Section: Introductionmentioning
confidence: 99%
“…1 However, it was not until recently that the combined detrimental effects of polyparasitism on childhood growth and development have emerged as a research focus. [2][3][4][5][6] The relationship between parasitic helminths and the subtle morbidities of undernutrition and anemia has been increasingly recognized in the past 20 years. 4,6 Previous studies have examined the overlapping effects of infection by soil-transmitted helminths (STHs), including hookworm, Ascaris lumbricoides, and Trichuris trichiura, on these outcomes, and more recently, studies have examined the combined effects of STH with schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, over the relevant economic time (i.e. intergenerational time), the transmission rate is determined by this feedback between economics and epidemiology and is thus endogenous to the system (Nokes et al 1992;Holding & Snow 2001;Ezeamama et al 2005;Fernando et al 2006). We can build such feedbacks into our model system by making the transmission rate a function of income and income a function of health:…”
Section: Income Effect Creates Feedback Between Disease Prevalence Anmentioning
confidence: 99%
“…This is due to both (i) a direct effect of health on labour productivity and, perhaps more importantly, (ii) an indirect effect on labour productivity through the effect of childhood health on the acquisition of human capital-the training and education of the workforce. Diseases such as malaria and parasitic worms, among others, are known to directly interfere with childhood learning processes, and therefore ultimately undermine long-term economic success (Nokes et al 1992;Holding & Snow 2001;Ezeamama et al 2005;Fernando et al 2006). …”
Section: Income Effect Creates Feedback Between Disease Prevalence Anmentioning
confidence: 99%